2019
DOI: 10.1038/s41598-018-36866-3
|View full text |Cite
|
Sign up to set email alerts
|

Marine biogenics in sea spray aerosols interact with the mTOR signaling pathway

Abstract: Sea spray aerosols (SSAs) have profound effects on our climate and ecosystems. They also contain microbiota and biogenic molecules which could affect human health. Yet the exposure and effects of SSAs on human health remain poorly studied. Here, we exposed human lung cancer cells to extracts of a natural sea spray aerosol collected at the seashore in Belgium, a laboratory-generated SSA, the marine algal toxin homoyessotoxin and a chemical inhibitor of the mammalian target of rapamycin (mTOR) pathway. We observ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
4
7
0
Order By: Relevance
“…There, we examined gene expression effects on A549 cells of the hYTX extract, next to pure hYTX and a natural SSA extract. Our previous findings [29], concerning the effects of YTXs on genes related to the mTOR pathway, corroborate our current results and provide additional support for the biogenics hypothesis.…”
Section: Effect On Mtor Pathway Activitysupporting
confidence: 91%
See 1 more Smart Citation
“…There, we examined gene expression effects on A549 cells of the hYTX extract, next to pure hYTX and a natural SSA extract. Our previous findings [29], concerning the effects of YTXs on genes related to the mTOR pathway, corroborate our current results and provide additional support for the biogenics hypothesis.…”
Section: Effect On Mtor Pathway Activitysupporting
confidence: 91%
“…Both suggestions imply a decreased bioavailability and lead to weaker effects. This conclusion, concerning the relative weaker effects of this hYTX extract, was also made in our previous study [29]. There, we examined gene expression effects on A549 cells of the hYTX extract, next to pure hYTX and a natural SSA extract.…”
Section: Effect On Mtor Pathway Activitysupporting
confidence: 70%
“…These studies showed, among others, that YTXs can downregulate the mTOR pathway, that is, the crucial cellular pathway in Moore's biogenics hypothesis. 34 The current study demonstrates the potential for exposure to YTXs through SSAs and therefore supports, combined with the above-cited effect studies, 29,32,33 the principles of the biogenics hypothesis. This highlights that, in addition to adverse effects of phycotoxins, SSAs can provide an exposure route for a whole spectrum of marine compounds with positive pharmacological effects.…”
Section: ■ Discussionsupporting
confidence: 83%
“…Moore 94 hypothesized that inhalation and ingestion (with upper respiratory tract mucus) of certain natural products, such as aerosolized harmful algal toxins (phycotoxins), may have direct effects on the body's molecular regulatory systems resulting in health benefits (eg, anti-inflammatory, anticancer, antiaging). 100 Recent support for this phytohormetic hypothesis has come from work by Asselman et al, 101 demonstrating that some phycotoxins in natural marine aerosols can inhibit mTOR and induce autophagy in cultured lung cells. Growth inhibition and apoptosis, both linked to mTOR pathway activity, may explain these effects, as yessotoxins were shown to downregulate this pathway.…”
Section: Hormesis and Autophagy In Animal And Human Evolutionmentioning
confidence: 99%